2019
DOI: 10.21603/2308-4057-2019-2-329-338
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal content in farmed rainbow trout in relation to aquaculture area and feed pellets

Abstract: Fish contamination by heavy metals, even at low levels, has an adverse effect on human health. Mercury (Hg), cadmium (Cd), and lead (Pb) are the most common heavy metals that contaminate sea foods. Rainbow trout is a fish species which is widely cultured in fresh water regions, e.g. in Yasuj, southwest of Iran. Heavy metal contamination was measured in three different culture areas (A, B, and C), with three different feed pellets used in Yasuj farms (I, II, and III). The sampling was conducted during February-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The carcinogenic and non-carcinogenic CDI values were obtained using the following formula [17]: Many recent studies used the Target Hazard Quotient (THQ) to peruse the potential non-carcinogenic effect of elements in the edible tissues of fish. In the present study, THQ was computed using the following equation to assess non-carcinogenic risks for trace elements in the fillet for adults [27][28][29][30][31][32][33]:…”
Section: Srudy Objects and Methodsmentioning
confidence: 99%
“…The carcinogenic and non-carcinogenic CDI values were obtained using the following formula [17]: Many recent studies used the Target Hazard Quotient (THQ) to peruse the potential non-carcinogenic effect of elements in the edible tissues of fish. In the present study, THQ was computed using the following equation to assess non-carcinogenic risks for trace elements in the fillet for adults [27][28][29][30][31][32][33]:…”
Section: Srudy Objects and Methodsmentioning
confidence: 99%
“…In addition, among the important factors that may affect the Cd level in tissues are the environment and sediment contamination. A previous study reported that the lowest Cd concentration was found in edible tissues of fish farmed in locations close to springs not polluted by sewage from urban or rural areas [38]. In Sudan, high levels of Cd and Pb were found in water and fish samples obtained from contaminated areas of the Nile River [39].…”
Section: Resultsmentioning
confidence: 94%
“…These results are in line with previous studies showing lower levels or even undetectable levels [47] and in contrast to other studies [43-44-17-28-46] showing Pb levels above the acceptable limit. The variations in heavy metal levels in fish feed are mainly affected by the different raw materials used in preparation of fish pellets [38]. If the trash fish already used contains high levels of metals, they may thus alter the levels of minerals in sediment and water.…”
Section: Meanmentioning
confidence: 99%
“…In addition, mercury compounds are highly soluble in water. Mercury is one of the most toxic elements in the environment, with organic and inorganic mercury being the main forms found in food samples [15].…”
Section: Introductionmentioning
confidence: 99%